From nanoscale heterogeneities to nanolites: cation clustering in glasses - Cormier, Laurent; Galoisy, Laurence; Lelong, Gérald; Calas, Georges (Comptes Rendus. Physique, 2023)
The structural behavior of cations in multicomponent oxide glasses cannot be described within a random network model, due to the presence of cation clusters that provide original properties. These clustering processes are even observed for cations that may occur at a percent level concentration, which makes it all the more spectacular. In particular, the structural and chemical characteristics of Zr$^{4+}$- and Fe$^{2+}$/Fe$^{3+}$-based clusters in (alumino)silicate glasses illustrate the link between the short-range order around cations and the formation of nanoscale heterogeneities. The structural characteristics of these Zr- or Fe-rich clusters are similar, as both are based on edge-sharing cation polyhedra. Cations may also occur in a network-forming position. In that case, cation sites are corner-linked with the silicate network. In such positioning, Pauling rules and local charge balance requirements will favor cations be diluted at a nanoscale. The topological constraints of these two types of local structure are stronger for the former than for the latter, as disorder effects are smaller for edge-sharing than for corner-sharing polyhedra. This may explain crystal nucleation during the growth of such ordered heterogeneities, giving rise to original properties that are illustrated in a large diversity of glassy materials encompassing high-tech glass-ceramics and volcanic glasses.